2014
DOI: 10.18632/oncotarget.2042
|View full text |Cite
|
Sign up to set email alerts
|

The stress phenotype makes cancer cells addicted to CDT2, a substrate receptor of the CRL4 ubiquitin ligase

Abstract: CDT2/L2DTL/RAMP is one of the substrate receptors of the Cullin Ring Ubiquitin Ligase 4 that targets for ubiquitin mediated degradation a number of substrates, such as CDT1, p21 and CHK1, involved in the regulation of cell cycle and survival. Here we show that CDT2 depletion was alone able to induce the apoptotic death in 12/12 human cancer cell lines from different tissues, regardless of the mutation profile and CDT2 expression level. Cell death was associated to rereplication and to loss of CDT1 degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…We observed that CDT2 depletion caused cSCC-selective DNA re-replication and DNA damage and that CDT2 knockdowneinduced death in cSCC cells was SET8-dependent ( Figure 5cee and Supplementary Figure S5a). This is consistent with a key role of rereplication in the antitumor activity of CDT2 suppression (Benamar et al, 2016;Olivero et al, 2014).…”
Section: Cullin-ring Ligase (Crl) 4 Cdt2supporting
confidence: 87%
“…We observed that CDT2 depletion caused cSCC-selective DNA re-replication and DNA damage and that CDT2 knockdowneinduced death in cSCC cells was SET8-dependent ( Figure 5cee and Supplementary Figure S5a). This is consistent with a key role of rereplication in the antitumor activity of CDT2 suppression (Benamar et al, 2016;Olivero et al, 2014).…”
Section: Cullin-ring Ligase (Crl) 4 Cdt2supporting
confidence: 87%
“…The CRL4 L2DTL E3 ligase can promote the ubiquitination of proteins in S phase and after DNA damage 49 . Numerous substrates of CRL4 L2DTL E3 ligase have been identified, such as CDT1, the CDK inhibitor, the histone methyltransferase Set8, the histone acetyltransferases GCN5, the checkpoint kinase CHK1 and the TOB anti-proliferative protein 54 . EED can strongly interact with CUL4A-DDB1 and participate in regulating the methylation of H3 histone at K9 and K27 49 .…”
Section: Wd40 Proteins Dna Damage and Repairmentioning
confidence: 99%
“…Overexpression of CDT2, one substrate receptor of CRL4, has been reported in many types of tumors such as breast [ 128 ], gastric [ 129 ], and ovarian carcinomas [ 121 ]. Silencing of CDT2 results in apoptotic death in cancer cells but not in non-transformed cells [ 130 ]. This suggests loss of CDT2 affects viability of cancer cells.…”
Section: Crl4 and Cancer Therapymentioning
confidence: 99%